Phytochemistry, pharmacology, and medicinal aspects of Allium fistulosum L.: A narrative review - Acharya Balkrishna, Mohini Chaudhary, Hemant Sharma, Deepika Srivastava, Ankita Kukreti, Ashwani Kumar, Vedpriya Arya (Journal of Applied Pharmaceutical Science, 2023)
Plants have been employed as traditional remedies for treating several ailments. Allium fistulosum L. is an important plant of the family Amaryllidaceae. In this review, its pharmacology, phytochemical, and medicinal aspects have been discussed in detail. It has been reported to be effective against diverse ailments, such as cold, influenza, abdominal pain, cephalgia, arthritis, etc. Allium fistulosum medicinal potential is attributed to flavonoids, furostanol saponins, cinnamic acid derivatives, thiolane-type sulfide, and several other bioactive compounds. Subsequently, pharmacological shreds of evidence revealed its anti-obesity, anti-viral, antimicrobial, anti-tumor, anti-oxidant, anti-inflammatory, and immunomodulatory activities. Interestingly, some recent studies also showed the immense potential of A. fistulosum to boost immunity against COVID-19. The bioactive composition of this plant should be subjected to clinical trials in the future for paving new aspects to develop a potential plant-based drug to treat human ailments.
Keywords: Welsh onion, Allium fistulosum, medicinal potential, bioactive compounds, pharmacological pro